Management of Teacher's Da'wah in Schools and Madrasas based on Pesantren - Rohmad, Muhammad Ali (Munazzama: Journal of Islamic Management and Pilgrimage, 2021)
This paper is a description of the results of research conducted to describe the management of teacher da'wah in Schools and Madrasas based on Pesantren. The research is carried out by going into the field directly to investigate phenomena that appear in the context of real life. The process is by constructing phenomena based on the data obtained and critical evaluation based on relevant theories so that the essence of events can be found to be compared with other data and with relevant theories so that their truth, robustness and suitability can be tested and concluded. The results of the study conclude that there is a different typology between the management of da'wah carried out by teachers in schools and madrasas based on pesantren. Teacher management in schools emphasizes the aspects of firmness and discipline. Meanwhile, the management of teacher da'wah in madrasas is dominant with aspects of responsibility and patience. The da'wah media used in the research area are oral, written, picture, and audio-visual.